Social Relations and Religious Law: The Phenomenon of Interfaith Marriage in Cisantana Village, Kuningan Regency, West Java - Aishah Khoirunnisa; Nur Nafisa Salsabila; Debagus; Amelia Rahmadani; Alamil Huda; Wisnu Uriawan (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2025)
This study explores the phenomenon of interfaith marriage in Cisantana Village, Kuningan. Regency, from the perspective of social relations and religious law. The research was motivated by increasing cases of interfaith marriage in a multicultural community that upholds strong religious values, often creating tension between belief and social harmony. Using a qualitative–participatory community engagement method with a legal sociology approach, data were collected through interviews, observation, and field documentation. The purpose is to analyze how interfaith marriage affects social interaction and how religious and state laws respond to it. Despite social and legal pressures, the results show that love is the primary motivation behind interfaith marriage. The Cisantana community demonstrates tolerance and adaptability, allowing interfaith families to coexist peacefully. This reflects that religious diversity, supported by inclusive social values, can foster harmony and strengthen social cohesion.